CMR and adverse clinical outcomes in peripartum cardiomyopathy - Agnes Koczo; Deeksha Acharya; Benay Ozbay; Rami Alharethi; Michael M. Givertz; Uri Elkayam; Erik B. Schelbert; Dennis M. McNamara; Timothy C. Wong (American Heart Journal Plus)
Background: Peripartum cardiomyopathy (PPCM) is associated with significant morbidity and mortality. Recent studies show recovery of left ventricular ejection fraction (LVEF) can still be associated with longitudinal adverse clinical outcomes. Cardiac MRI (CMR) may yield additional prognostic parameters of serious adverse outcomes (SAE) beyond LVEF. Methods: Individuals with PPCM and CMR within 3 months of diagnosis were analyzed from the Investigations in Pregnancy Associated Cardiomyopathy (IPAC) trial and our institution from 2010-present. Indexed left ventricular (LV) mass, ventricular volumes, cardiac output, global longitudinal strain (GLS), extracellular cellular volume (ECV) as well as epicardial fat volume (EFV) were analyzed. SAEs included left ventricular assist device (LVAD), heart transplant and death. CMR parameters were compared between SAE and no SAEs groups by non-parametric techniques. Results: Among 51 individuals with mean age of 31 years at diagnosis, 6/51 (12 %) experienced 11 adverse outcomes. EF at time of CMR (15.0 vs 37.3 %, p < 0.001), peak LV GLS (−4.1 % vs −10.0, p = 0.002) ECV (43.6 vs 28.2, p = 0.02) and stroke volume differed significantly among groups. In univariate regression analysis, worse LVEF, lower peak GLS and greater LVESVi were predictive of adverse outcomes. Conclusion: Prior studies found baseline LVEF by echo is a predictor of serious adverse outcomes. CMR identified significantly different baseline LVESVi peak LV GLS and ECV among PPCM with SAEs vs no SAEs. If confirmed in larger studies, diffuse myocardial fibrosis may represent a therapeutic target in PPCM.